Optimalisasi Pemasaran Digital dengan Integrasi Media Sosial untuk Meningkatkan Penjualan Online UMKM YANI Store - Hasibuan, Ulfa Suryani; Annas, Firdaus; Rizky, Alya (Yayasan Lembaga Studi Makwa, 2023)
The development of digital technology has opened up great opportunities for micro, small and medium enterprises (MSMEs) to expand their market reach through online marketing strategies. This article aims to examine the optimization of OpenCart-based digital marketing which is integrated with social media, such as Instagram, TikTok, and WhatsApp, to support sales of YANIStore Shop MSME products. This research aims to provide an understanding of how the integration of e-commerce technology with social media can increase the effectiveness of marketing and product sales. The research method used is a qualitative descriptive study, with data collection in the form of documentation of marketing activities, customer interactions and sales transactions via the OpenCart platform and social media. Analysis was carried out to evaluate the effectiveness of the integration of OpenCart as a sales management platform with social media as a promotional tool. The research results show that the synergy between OpenCart and social media can increase product visibility, expand the customer base, and increase sales conversions. This article concludes that this technology integration is an effective strategy to support the growth of MSMEs in the digital era. Recommendations are also given to optimize the use of OpenCart and social media in increasing the competitiveness of MSMEs.